(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
A new lupane type triterpene (1), together with betulinic acid (2), friedelin (3), aristolochic acid I (4), alpinumisoflavone (5) and 4â€™-O-methylepinumisoflavone (6) have been isolated from the leaves of Thecacoris annobonea. The structure of the new compound was elucidated on the basis of 1 and 2D NMR experiments. The isolated compounds were evaluated for their phytotoxicity and antimicrobial activity. 1 exhibited significant antimicrobial activity at 30 Î¼g/ml and compounds 1, 2, 3, 4, 5 and 6 inhibited root growth lettuce at 100 Î¼g/ml.Â